Considerações sobre a federalização e a gestão compartilhada do território na Amazônia brasileira - Gilberto de Miranda Rocha; Sabrina Fortes e Silva Gonçalves (Confins)
Territorial federation has since the 1970s been a legal and political instrument within the framework of the Brazilian State organization in different governments (military and civil) for regional integration and for the appropriation and use of the region's natural resources. For at least the last forty years, federal intervention has been the cornerstone of successive regional development plans, programs and projects. The political and institutional reforms established with the promulgation of the 1988 Federal Constitution redefined intergovernmental relations. The shared management of the territory emerges as a proposition from then on, pointing to the valorization of the subnational spheres of government (states and municipalities) in subjects pertinent to territorial organization, use of natural resources and mechanisms of social and political regulation.